Mechanism and Regulation of Silique Dehiscence, Which Affects Oil Seed Production - Yu, Yan-Kun; Li, Yu-Long; Ding, Li-Na; Sarwar, Rehman; Zhao, Feng-Yun; Tan, Xiao-Li (Frontiers in Plant Science, 2020)
Silique dehiscence is an important physiological process in natural growth, which enables mature seeds to be released, to realize their own reproduction and expand the scope of survival of future generations. In agricultural production, the time and degree of silique dehiscence affect the harvest and processing of crops. Besides, premature silique dehiscence leads to seeds massively shedding before harvest, resulting in a substantial reduction in yield. Too late silique dehiscence is not conducive to harvest, and grain weight and oil content will also be reduced for the respiratory consumption of seeds. In this paper, mechanism and regulation of silique dehiscence and its application in agricultural production was overviewed.